Classificação de cônicas e quádricas - Oyafuço, Keide Tukamoto [UNESP] (2015)
The main objective of this study is to classify the conics curves and the quadrics surfaces that are represented through equations Ax2 + By2 + Cz2 + Dxy + Exz + Fyz + Gx + Hy + Iz + J = 0 whit A,B,C,D,E.F,G,H, I, J 2 R. Before the classification of these curves and surfaces we will present some concepts and results of Linear Algebra such as the vector spaces with an inner product, adjoints operators and the bilinear forms. The concepts and results presented will be the supported for the classification of the conics as of the quadrics. Beyond the classification of the conics and the quadrics, we go to present a proposal of activity with software GEOGEBRA so that students of Ensino Médio better understand the concept of the conics (ellipse, hyperbola and parabola)